EXPLORING THE IMPACT OF ACADEMIC STRESS ON THE ACADEMIC PERFORMANCE OF UNDERGRADUATES STUDENTS IN LAHORE’S PUBLIC UNIVERSITIES - Wajeeha Rahat; Dr. Ismat Bano (International Journal of Contemporary Issues in Social Sciences, 2024)
This quantitative research study aimed to investigate the Impact of Academic Stress on the Academic Performance of Undergraduates students in Lahore’s Public Universities. The research included both male and female students and employed a stratified sampling method, resulting in a well-balanced sample of 300 students, equally divided between genders. Data was collected during the students’ sixth semester within the education department, utilizing questionnaires to gather information on demographics, academic stress, and performance. Data analysis was carried out using SPSS software, with correlation analysis used to explore the potential relationship between academic stress and academic performance. Ethical considerations were strictly maintained to ensure participant confidentiality and informed consent. The findings of the study indicated an extremely weak negative correlation between academic stress factors and academic performance, with a Pearson Correlation coefficient of -0.003. The non-significant p-value of 0.966, coupled with the sample size of 300 for both variables, suggests that there is minimal, if any, discernible relationship between sources of stress and academic performance within the context of this study. Gender-based differences in academic performance were also explored, and no significant distinctions were found between male and female students. Effect sizes demonstrated a substantial impact on academic performance. These findings contribute to a deeper understanding of the relationship between academic stress and performance, particularly within the context of public universities in Lahore.